Performance of Sediment Microbial Fuel Cell (SMFC) System using Carbon Fiber Electrodes - Setianto Setianto; Abdurrohman Abdurrohman; Otong Nurhilal; Nendi Suhendi; Darmawan Hidayat (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
A microbial fuel cell (MFC) is a type of biological fuel cell that converts chemical energy stored in an organic mixture into electrical energy that further penetrates the catalytic reaction of microorganisms. The Sediment Microbial Fuel Cell (SMFC) is a microbial fuel cell that can convert complex organic matter in the sediment to generate electrons. This research was conducted by designing a single chamber SMFC power generation system using graphite and carbon fiber electrodes. As a result, the single-chamber SMFC system with carbon fiber electrode performed better with an average electric power output of 561.11 mW for 21 days.